Penerapan Sistem Absensi Finger Print Terhadap Kinerja Pegawai Melalui Displin Kerja Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sumenep - Syaiful Anwar; Moh. Kurdi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Work discipline is the beginning of the process of improving employee performance, therefore employee discipline needs to be maximized to employees either through rules or the use of tools that can bind and reduce fraud from the employees themselves, in this case in every organization, agency, company has used a lot. a tool in the form of a fingerprint attendance system. Increasing discipline by using the fingerprint attendance system is inseparable from the obstacles that occurred previously in the form of the number of employees who are still not maximal in terms of their attendance levels and carrying out their duties. Therefore, researchers want to know how the effect of applying the fingerprint attendance system on work discipline on employee performance in Dispendukcapil of Sumenep Regency. The purpose of this study was to determine and analyze the effect of fingerprint application on employee performance through work discipline at the Dispendukcapil of Sumenep Regency. The analysis in this study uses path analysis. The results of the study indicate that the fingerprint has a significant relationship to the performance of both employees through employee work discipline at the Dispendukcapil of Sumenep Regency. This is very good for improving employee performance.